2014
DOI: 10.14348/molcells.2014.0207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Profiling of Pancreatic Ductal Adenocarcinoma Cell Lines

Abstract: Pancreatic cancer is one of the most fatal cancers and is associated with limited diagnostic and therapeutic modalities. Currently, gemcitabine is the only effective drug and represents the preferred first-line treatment for chemotherapy. However, a high level of intrinsic or acquired resistance of pancreatic cancer to gemcitabine can contribute to the failure of gemcitabine treatment. To investigate the underlying molecular mechanisms for gemcitabine resistance in pancreatic cancer, we performed label-free qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…This approach was particularly powerful as it leveraged information from 48 experiments (4 drug screens x 3 replicates x 2 cell lines x 2 sgRNAs). We found L2FC sums to be weakly correlated across cell lines (rho=0.014, P=0.034), likely a reflection of strong phenotypic and genetic differences found between our two cell lines (Kim et al, 2014).…”
Section: Crispr Screening Reveals Drug Resistance Genesmentioning
confidence: 78%
See 1 more Smart Citation
“…This approach was particularly powerful as it leveraged information from 48 experiments (4 drug screens x 3 replicates x 2 cell lines x 2 sgRNAs). We found L2FC sums to be weakly correlated across cell lines (rho=0.014, P=0.034), likely a reflection of strong phenotypic and genetic differences found between our two cell lines (Kim et al, 2014).…”
Section: Crispr Screening Reveals Drug Resistance Genesmentioning
confidence: 78%
“…The second general observation was a relatively weak correlation between replicate reproducibility and gene significance levels across cell lines. While this observation may be partially explained by methodological covariates like selection strength ( Figure S4), it is also likely that strong genetic and phenotypic differences observed between these cell lines (Kim et al, 2014) permit different mechanisms of chemoresistance. A gene capable of modulating chemosensitivity across every PDAC cell line would be an ideal target, however, our data suggests that this is not a realistic expectation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chemotherapy or radiotherapy treatments only provide a modest benefit in survival . Previous studies on the intrinsic resistance of different PC cell lines to gemcitabine, distinguished chemosensitive cells with epithelial‐like phenotype from more chemoresistant cells with mesenchymal‐like phenotype . Gene expression profiling showed that spontaneous chemoresistance of the cell lines was associated with low expression of E‐cadherin and high expression of ZEB‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Previous studies on the intrinsic resistance of different PC cell lines to gemcitabine, distinguished chemosensitive cells with epithelial-like phenotype from more chemoresistant cells with mesenchymal-like phenotype. 28 Gene expression profiling showed that spontaneous chemoresistance of the cell lines was associated with low expression of E-cadherin and high expression of ZEB-1. 29 To investigate acquired resistance mechanisms of PC cells of epithelial-like or mesenchymal-like phenotypes upon sequential chemotherapy regimens, pancreatic tumor cells belonging to these different phenotypes were subjected to a chronic treatment by gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2/ARE signalling also controls the expression of cytosolic thioredoxin (TXN1 gene), thioredoxin reductase (TXNRD1 gene), and sulfiredoxin (SRXN1 gene), all of which reduce oxidised protein thiols (Lu and Holmgren, 2014). In PDAC, the glutathione-based antioxidant system contributes to gemcitabine resistance (Kim et al, 2014), and the thioredoxin-based system supports cancer cell survival (Yan et al, 2009).…”
Section: Cytoprotection By Are-driven Genesmentioning
confidence: 99%